Functional Antibodies and Innate Immune Responses to WRSS1, a Live Oral Shigella sonnei Vaccine Candidate, in Bangladeshi Adults and Children. (10th August 2021) - Sarker, Protim; Mily, Akhirunnesa; Ara, Anjuman; Haque, Farjana; Maier, Nicole; Wierzba, Thomas F; Walker, Richard I; Venkatesan, Malabi M; Raqib, Rubhana
Abstract: Background: We demonstrated in a randomized placebo-controlled trial that WRSS1, a live oral Shigella sonnei vaccine candidate, is safe in Bangladeshi adults and children, and elicits antigen-specific antibodies. Here, we describe functional antibody and innate immune responses to WRSS1. Methods: Adults (18–39 years) and children (5–9 years) received 3 doses of 3 × 10 5 or 3 × 10 6 colony forming units (CFU) of WRSS1 or placebo, 4 weeks apart; children additionally received 3 × 10 4 CFU. Blood and stool were collected at baseline and 7 days after each dose. Functional antibodies were measured using serum bactericidal antibody (SBA) assay. Cytokine/chemokine concentrations were measured in lymphocyte cultures. Host defense peptides LL-37, HBD-1, and HD-5 were analyzed in plasma and stool. Results: Children showed increased SBA titers over baseline after the third dose of 3 × 10 6 CFU ( P = .048). Significant increases of Th-17 and proinflammatory cytokines (TNF-α, G-CSF, MIP-1β), and reduction of anti-inflammatory and Th2 cytokines (IL-10, IL-13, GM-CSF) were observed in children. Plasma HBD-1 and LL-37 decreased in children after vaccination but were increased/unchanged in adults. Conclusions: Functional antibodies and Th1/Th17 cytokine responses in children may serve as important indicators of immunogenicity and protective potential of WRSS1. Clinical Trials Registration : NCT01813071.